CP-106 Pharmaceutical validation: assessing a computerised asitance programme. (25th February 2017) - Martin, I; Martí, C; Sánchez, J; Llorente, M; Barreda, D
Abstract : Background: Traditionally, pharmaceutical validation (PV) has been done by pharmacists, who analyse treatments prescribed to hospitalised patients using their own criteria, based on their knowledge or bibliography. On the other hand, medication errors are one of the main causes of adverse events related to healthcare. New technologies may help professionals to minimise risk in treatments for patients. Purpose: To evaluate the increase in pharmacotherapeutic recommendations (PR) after implementation of a computerised assistance programme (CAP) for PV. Material and methods: This was an ambispective, descriptive, quasi-experimental study over 2 months, carried out in several clinical services assigned unidoses drug distribution, with manual prescriptions, at a level II hospital. The study consisted of two phases: period A (before CAP) in August 2016, involving only manual validation; period B (after CAP) in September 2016, with manual validation plus support software (AltoMedicamentos). PV was performed using the software FarmaTools-Dominion, recording PR, which were communicated to physicians. Variables collected: demographics (sex, age), clinics (clinical service), pharmacotherapeutic (therapeutic group involved, type of PR, degree of acceptance) and origin (manual validation/AltoMedicamentos). PR classification was based on the Iaser method. Data processing: Microsoft Office Excel. Results: 279 PR were made over the 2 months (99 in period A; 181 in period B), which represented an increase of 81%. They were related to 196 patients (82 A; 114 B), 51% men (42.7% A; 57% B), median age 80 (81 A: 79 B). The main clinical services were general surgery (100 :38 A; 62 B), traumatology (47: 13 A; 34 B) and internal medicine (46: 16 A; 30 B) The majority of therapeutic groups involved were analgesics and antipyretics (38 B) and proton pump inhibitors (34: 16 A; 18 B). The mainly PR motives were change dosing regimen/route of administration/sequential therapy (131: 35 A; 96 B), alert days/interaction/duplicity (70: 35 A; 35 B) and replacement of a drug not included in the hospital guide for an alternative (51: 20 A; 31 B). According to degree of acceptance, 61% were accepted by physicians (50.5% A; 57.7% B), excluding PR not assessable (10%). Change dosing regimen was the most accepted type of PR (47% A, 59.7% B). A comparison between these two periods showed that about 37% of the increase from period B to period A was due to AltoMedicamentos. Conclusion: A CAP for PV is an extra support for pharmacists, but there is not enough evidence to affirm that it has created an improvement in relation to the control month regarding an impact on PR. A larger prospective study is needed to provide more evidence. No conflict of interest